Variables related to perceived stress and resilience among international migrants: a multicenter study (AFFAIR Project) - Barreto, Mayckel da Silva; Barbieri-Figueiredo, Maria do Céu; Garcia-Padilla, Francisca Maria; Saenz Mendia, Raquel; Silva, Renan Alves; Sá, Florinda Laura Ferreira Rodrigues Galinha De; Almeida, Camila Aparecida Pinheiro Landim; Campos, Maria Joana; Lise, Fernanda; Marcon, Sonia Silva (FapUNIFESP (SciELO), 2024)
ABSTRACT Objective: To identify variables related to perceived stress and resilience of international migrants. Method: Multicenter, observational, cross-sectional study carried out with 403 migrants residing in Brazil, Spain, or Portugal. The following instruments were used to collect data: Perceived Stress Scale and Resilience Scale. Student's t-test and analysis of variance were applied in the analysis. Results: Perceived stress was related to: living in Brazil or Portugal; shorter stay in the host country; being black or brown; and having no religion. Greater resilience was related to: not being divorced; having less education and lower family income; being from developing countries; living in Spain; and having a religion. Conclusion: Aspects such as host and origin country, skin color, income, marital status, education, length of stay in the host country, and religion are related to the level of stress and/or resilience of migrants. Knowing this profile is useful for developing public integration policies and interventions that seek to reduce stress and improve resilience.
Variáveis relacionadas ao estresse percebido e à resiliência entre migrantes internacionais: estudo multicêntrico (AFFAIR Project)
Keywords: Resilience; Psychological; Stress; Transients and Migrants; Emigration and Immigration; Migrant-Receiving Society; Multicenter Study